Precision Horticulture: A Mobile System to Support Agriculture Yield. - Adwan, Kamal A. M. (2007)
The rapid advancement in information technology has changed our life; it has a major impact on the environment around us. Mobile and wireless technology have become an important medium for people to communicate. This research used the Object Oriented Methodology (OOM) as a guideline. The goal of this research project is to design and develop a mobile system to improve agriculture yield, using Wireless Application Protocol (WAP) technology that supports the use of smart phones devices for the benefit of public and rural advancement. A brief overview of several mobile technologies is presented. The development process and problems encountered when designing the prototype of the Mobile System to Improve Agriculture yield is discussed in this paper. The usability testing conducted in this research revealed that the WAP site application is effective and should be implemented for this system.